Truman's NTA UGC NET SET teaching and research aptitude Paper1 - Sajit Kumar (New Delhi Danika Publishing Company, 2023)
Best Selling Book for NTA UGC NET Exams. Covering new syllabus applicable from June, 2019 onward exams and new model papers ideal for SET (State Eligibility Tests) also.